Federal Spaces, Local Conflicts: National Parks and the Exclusionary Politics of the Conservation Movement in Ontario, 1900-1935 - Sandlos, John (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2005)
AbstractThe historical displacement of indigenous and non-Native people from national parks and nature preserves has often been analyzed as a deliberate imposition of state authority over local people living in rural and hinterland regions. The cases of Point Pelee and Georgian Bay Islands National Parks indicate that local people had considerable influence over the siting and management policies applied to parks and protected areas in the early twentieth century. Although the federal government did attempt to either expel or severely curtail the wildlife harvesting activities of Aboriginals and non-Aboriginals living within the national parks during this period, such policies were often the result of lobbying from local conservation groups intent on saving threatened wildlife populations or business promoters hoping to stimulate the local tourist economy through the creation of a public pleasuring ground. This paper argues that the management frameworks governing Point Pelee and Georgian Bay Islands National Parks were not the product of narrow state interests, but of a much broader policy community composed of local and state actors hoping to shape the park environments to suit their own political priorities.